Is the Outcome Indicator “3rd/4th Degree Perineal Tear in Spontaneous Singleton Births” a Reliable Quality Parameter in Obstetrics? - Franz, H. B. G.; Erxleben, C. W. J. (Geburtshilfe und Frauenheilkunde, 2015)
Obstetric sphincter damage is the most common cause of fecal incontinence in women. Between one-third and two-thirds of women who sustain a recognized third-degree tear during delivery subsequently suffer from fecal incontinence. We should therefore try to reduce the rate of high-grade tears as much as possible. But this rate can only be used as an outcome indicator for the quality of obstetric departments if the recognition and classification of sphincter injury is similar across departments in different hospitals.
Keywords: delivery; fecal incontinence; tear; external anal sphincter; quality